2021
DOI: 10.18632/aging.202913
|View full text |Cite|
|
Sign up to set email alerts
|

Potential reversal of epigenetic age using a diet and lifestyle intervention: a pilot randomized clinical trial

Abstract: Manipulations to slow biological aging and extend healthspan are of interest given the societal and healthcare costs of our aging population. Herein we report on a randomized controlled clinical trial conducted among 43 healthy adult males between the ages of 50-72. The 8-week treatment program included diet, sleep, exercise and relaxation guidance, and supplemental probiotics and phytonutrients. The control group received no intervention. Genome-wide DNA methylation analysis was conducted on saliva samples us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
152
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(158 citation statements)
references
References 43 publications
6
152
0
Order By: Relevance
“…For example, Sae‐Lee and colleagues investigated folic acid and vitamin B12 supplementation in a randomized trial including 44 participants (+13 participants from a non‐randomized trial), concluding that the slowing down of the DNAm aging is gender‐ and MTHFR genotype‐specific (Sae‐Lee et al, 2018 ). More recently, Fitzgerald and colleagues provide evidence of reversal epigenetic clocks improving diet and lifestyle in a randomized trial including 38 participants (Fitzgerald et al, 2021 ). Although there is strong evidence that physical exercise has favorable effects on epigenetic mechanisms (Ferioli et al, 2019 ), there is a lack of intervention studies on increasing physical activity associated with longitudinal measures of epigenetic clocks and aging‐related epigenetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sae‐Lee and colleagues investigated folic acid and vitamin B12 supplementation in a randomized trial including 44 participants (+13 participants from a non‐randomized trial), concluding that the slowing down of the DNAm aging is gender‐ and MTHFR genotype‐specific (Sae‐Lee et al, 2018 ). More recently, Fitzgerald and colleagues provide evidence of reversal epigenetic clocks improving diet and lifestyle in a randomized trial including 38 participants (Fitzgerald et al, 2021 ). Although there is strong evidence that physical exercise has favorable effects on epigenetic mechanisms (Ferioli et al, 2019 ), there is a lack of intervention studies on increasing physical activity associated with longitudinal measures of epigenetic clocks and aging‐related epigenetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…Horvath’s model has been widely used as it is seen as the state-of-the-art pan-tissue epigenetic clock for humans [1316]. Therefore, it is essential to contrast it with AltumAge.…”
Section: Resultsmentioning
confidence: 99%
“…AltumAge is a better age predictor than state-of-the-art epigenetic clocks Horvath's model has been widely used as it is seen as the state-of-the-art pan-tissue epigenetic clock for humans [13][14][15][16]. Therefore, it is essential to contrast it with AltumAge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, intrinsic epigenetic age acceleration, a measure of cell-intrinsic aging based on a modified version of Horvath's clock independent of blood cell composition (Chen et al 2016), is negatively associated with poultry intake (Quach et al 2018). Fitzgerald et al reported a reduction of Horvath's DNA methylation age of 1.96 years measured from saliva samples in a cohort that followed an 8-week diet and lifestyle intervention that targeted sleep, exercise, stress, and nutrition (Fitzgerald et al 2021).…”
Section: Nutritional Effects On the Epigenomementioning
confidence: 99%